Variation in Bat Guano Bacterial Community Composition With Depth - Newman, Molli M.; Kloepper, Laura N.; Duncan, Makenzie; McInroy, John A.; Kloepper, Joseph W. (Frontiers in Microbiology, 2018)
Bats are known to be reservoirs for a variety of mammalian pathogens, including viruses, fungi, and bacteria. Many of the studies examining the microbial community inhabiting bats have investigated bacterial taxa found within specific bat tissues and isolated bat guano pellets, but relatively few studies have explored bacterial diversity within bat guano piles. In large bat caves, bat guano can accumulate over time, creating piles several meters deep and forming complex interactions with coprophagous organisms in a habitat with low light and oxygen. As the guano decays, the nutrient composition changes, but the bacterial communities deep within the pile have not been characterized. Here, we assess the bacterial communities across varying depths within the guano pile using both culture-independent and culture-dependent methods. We found that although similar taxa are found throughout the guano pile, the relative abundances of taxa within the pile shift, allowing certain taxa to dominate the bacterial community at varying depths. We also identified potential bacterial functions being performed within the bat guano as various depths within the pile and found little variation in terms of the dominant predicted functions, suggesting that although the relative abundances of bacterial taxa are changing, the functions being performed are similar. Additionally, we cultured 15 different bacterial species, including two not present in our culture-independent analysis, and discuss the pathogenicity potential of these taxa. This study represents the first characterization of the bacterial community from the extreme environment within a bat guano pile and demonstrates the potential for bat caves as resources for identifying new bacterial species.